Sigma Force : Sandstorm - Book 1 Book 1 - Rollins, James. 1961-; Czajkowski, James (New York : Harper, an imprint of HarperCollinsPublishers, 2011)
Twenty years after a wealthy British financier disappears near the site of a lost fabled city, the mans daughter leads an expedition of scientists in search of the city, which harbors a powerful but dangerous energy source.
Keywords: Scientific expeditions -- Fiction; Missing persons -- Fiction; British -- Oman; Fiction; Antimatter -- Fiction; Sandstorms -- Fiction; Ubar (Extinct city) -- Fiction; Oman -- Fiction; Thriller